Peritalar Parameters in Medial Column Collapse: 3D Analysis Distinguishing Midfoot Arthritis and Progressive Collapsing Foot Deformity - Mohamad R. Issa MD; Tommaso Forin Valvecchi MD; Emily Joan Luo BS; Jeffrey Liles MD; Antoine Acker MD; Andrew Hanselman MD; Karl M. Schweitzer MD, FAAOS; Chien-Shun Wang MD; Victor Silvinskis BS; Cesar de Cesar Netto MD, PhD (Foot & Ankle Orthopaedics)
Category: Midfoot/Forefoot; Hindfoot Introduction/Purpose: Midfoot arthritis (MA) and progressive collapsing foot deformity (PCFD) are both entities characterized by biomechanical changes of the foot leading to collapse of the medial arch. The effect of PCFD on peritalar dislocation/subluxation has been described extensively and is a critical consideration in preoperative planning of deformity correction. While midfoot arthritis has been previously associated with subluxation of the midfoot joints such as the naviculocuneiform and tarsometatarsal joints, no studies have evaluated the effect of midfoot arthritis medial column collapse on peritalar parameters. The primary objective of this study was to compare the extent of medial arch collapse in MA and PCFD and correlate these parameters with peritalar changes. Methods: This is a retrospective comparative study identifying patients with PCFD and MA. PCFD was defined as a known history of flatfoot deformity and symptomatic progression of medial arch collapse. Midfoot arthritis was identified through radiological findings along with patient-reported symptomatic medial arch collapse. Patients with both flat foot deformity and radiological findings of midfoot arthritis were excluded. All patients underwent foot/ankle Weightbearing computed tomography (WBCT). Manual and semi-automated 3D measurements of the middle facet subluxation percentage, middle facet incongruence angle, foot & ankle offset, forefoot arch angle, and transverse arch plantar angle were performed. Measurements were done independently by two fellowship-trained readers. Variables were assessed for normality (Shapiro-Wilk) and compared using Paired T-tests or Wilcoxon signed rank test. P-values of 0.05 or less were considered significant. Results: A total of 28 feet were analyzed (14 extremities with PCFD and 14 extremities with MA). The difference in middle facet subluxation percentage and middle facet incongruence angle were statistically significant between the 2 groups favoring more peritalar subluxation in the PCFD group as compared to the MA group (38 vs 14.1 p-value < 0.001 and 12.5 vs 4.1 p-value < 0.001, respectively). The forefoot arch angle was significantly lower in the PCFD group (2.8 vs 6.6, p-value < 0.005) No significant difference was identified in the transverse arch plantar angle between the groups (125.5 vs 121.6, P-value: 0.2). Conclusion: In this retrospective comparative study, midfoot arthritis was found to have a limited effect on peritalar parameters in the setting of medial arch collapse. This study demonstrated that the deformity associated with midfoot arthritis is confined to the medial column and does not affect peritalar subluxation, unlike PCFD. These data demonstrate for the first time that midfoot arthritis and PCFD require distinct approaches in order to address medial column stability in order to achieve the required restoration in foot alignment.